Strategic entrepreneurship model for Malaysian Economic Transformation Programme / Profesor Madya Dr Amran Awang, AMP … [et al.] - Awang, Amran; Khalid, Shaiful Annuar; Kassim, Azizan; Selamat, Sarah Mardhiah; Mohammad Nor, Azura; Shukor, Najihah; Shaari, Ahmad Zakhwan Firduase (Research Management Institute (RMI), 2015)
Studies in strategic entrepreneurship have been steadily investigated since early 2000 when Hitt et al. (2003) proposed a conceptual framework in their textbook. However, much still unknown in capitalizing SE as a body of knowledge in entrepreneurship literatures. Most of the studies (e.g. Shepherd & Wilklund, 2009; Schindehutte & Morris, 2009; Hitt et al., 2011ab) however belief that SE has considerable impact on firms' growth, CA, opportunity advantage, value and wealth creation. SE is an integrative model of strategic management and entrepreneurship whereby they capitalize on firms' behavioral aspect that will transform their internal resources (transforming its product, markets, internal processes and so on) to better future and higher industrial standard. SE can be explained by any one of the five forms, strategic renewal, sustained regeneration, domain redefinition, organizational rejuvenation, and business model reconstruction (Covin & Miles, 1999). Works in SE show a steady increments but wide gap still wide open, more ground works in concept and model development are still under develop. Among others a model of Ireland, Hitt and Sirmon (2003) proposed four dimensions (1) the entrepreneurial mindset, culture and leadership, (2) the strategic management of organizational resources, (3) application of creativity,and (4) development of innovation. Kyrgidou and Hughes (2010) critized the model as lacking in robustness as required in capturing the gestalt of SE. Supporting the argument were studies that suggested the model should uphold SE as broader in scope, multilevel and more dynamic compared to original conceptualization (Chiles, Bluedorn & Gupta, 2007; Hitt, Beamish, Jackson & Mathieu, 2007; Rindova, Barry & Ketchen, 2009). Recently, Hitt, et al. (2011) proposed input-processes-output model of SE that incoporate multilevel and broader domain, environmental influences, RO and three levels of outcome.